Experiences Of Nurses Regarding Communication With Mechanically Ventilated Patients In The Intensive Care Units - Nadia, .; Naz, Najma; Muhammad, Dildar; Sajid, Shazia; Rahim, Tariq; Ajmal, Hina; Kalsoom, Bushra (Pakistan Journal of Health Sciences, 2023)
Nurses’ communication with mechanically ventilated patients (MVPs) is very imposrtant assuring respect and dignity of the patients and dealing the patient like a human being rather than a body. OBJECTIVE: To explore the experiences and perspectives of nurses regarding communication with Mechanically ventilated patienst in the intensive care units of Islamabad Pakistan. STUDY METHODS The qualitative phenomenological study was conducted on ten participants, selected through purposive sampling technique for individual in-depth interviews. RESULTS: Six major themes of the study were recognition of communication experiences is essential for care, construction and interpretation of communication is situational, lack of speaking power led to feelings of powerless and frustration, nurses’ responsibilities in the situation of critical care, impacts of verbal communication on the mechanically ventilated patient, and need for acceptance of knowledge and skills acquisition. CONCLUSION The current study highlighted experiences of nurses regarding communication with mechanically ventilated patients in the ICUs. The study findings further suggested the areas for improvement of nurses’ communication with MVPs